MEMBANGUN MINAT BUDAYA LITERASI MELALUI CIPPSI DAN MENCERAH SEBAGAI WUJUD MERDEKA BELAJAR DI SMAN 1 KADEMANGAN - Purwati, Endah (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this study was to inform students' interest in literacy in cipta puisi competitions (CIPPSI) and menulis cerita sejarah (MENCRAH) at SMAN 1 Kademangan to build a literacy culture. The CIPPSI competition was attended by 526 students and the BRIGHT competition was attended by 506 students. This research is a descriptive quantitative research using a survey through a questionnaire. Questionnaires are given to students after carrying out the competition by way of students being given articles for reading material and then filling out a questionnaire. 551 students have filled out the questionnaire with the results that 547 students (99%) stated that they understood the contents of the reading and were happy and 4 students (1%) did not understand the reading. 544 students (98,7%) already have plans to read again and 7 (1,3%) have no plans to read. Based on the results of the questionnaire, it is shown that the literacy culture through CIPPSI and MENCERAH has been built at SMAN 1 Kademangan as an embodiment of independent learning. The CIPPSI and MENCERAH competitions can encourage students to be free to seek ideas, and to be active outside the classroom. Collaboration in Bahasa Indonesia, Sejarah and PPKn, can be part of the literacy learning process.